The energetics of ultra-endurance running - Lazzer, S.; Salvadego, D.; Rejc, E.; Buglione, A.; Antonutto, G.; Di Prampero, P. E. (European Journal of Applied Physiology, 2012)
Our objective was to determine the effects of long-lasting endurance events on the energy cost of running (C r), and the role of maximal oxygen uptake (VO2max), its fractional utilisation (F) and C r in determining the performance. Ten healthy runners (age range 26-59 years) participated in an ultra-endurance competition consisting of three running laps of 22, 48 and 20 km on three consecutive days in the North-East of Italy. Anthropometric characteristics and VO2max by a graded exercise test on a treadmill were determined 5 days before and 5 days after the competition. In addition, C r was determined on a treadmill before and after each running lap. Heart rate (HR) was recorded throughout the three laps. Results revealed that mean C r of the individual laps did not increase significantly with lap number (P = 0.200), thus ruling out any chronic lap effect. Even so, however, at the end of lap 3, C r was 18.0% (P < 0.001) greater than before lap 1. In addition, a statistically significant acute lap effect on C r was observed at the end of the second and third laps (by 11.4 and 7.2%, respectively). The main factors determining performance were VO2max, F, as estimated from the average HR, and the average C r-mean throughout the three laps; the grand average speed over the three laps being described by v end-mean = F × VO2max × C r-mean-1. We concluded that (1) the substantial increase of C r-mean during the competition yields to marked worsening of the performance, and (2) the three variables F, VO2max and C r-mean combined as described above explaining 87% of the total competition time variance.